PENGEMBANGAN LKPD THINK TALK WRITE BERGAMIFIKASI DASHBOARD SHINY UNTUK MENULIS NARASI SEJARAH KELAS V SD - Istianah, Devi; Muktadir, Abdul; Gumono; Agusdianita, Neza; Juarsa, Osa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low narrative-writing skills of fifth-grade students at SD Negeri 77 Kota Bengkulu, where the student worksheets (LKPD) used were still conventional, containing only ordinary essay questions without a structured writing process, and the learning media applied were static and unattractive. Curriculum analysis further revealed that the teacher's lesson plans had not been fully aligned with the Merdeka Curriculum's Learning Outcomes. Consequently, students experienced difficulties determining themes, arranging outlines, applying correct spelling, constructing sentence structures, and maintaining text coherence. This research aimed to develop a gamified Think Talk Write (TTW) student worksheet supported by a Shiny Dashboard for writing historical narrative texts about the Red-and-White Flag, and to describe its characteristics, feasibility, user response, and effect on students' narrative-writing profile. The study employed the Research and Development (R&D) method with the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation. Subjects were 40 fifth-grade students, divided into class VA as a limited-trial group (n = 20) and class VB as the main research class (n = 20), selected through total sampling. Data were collected through curriculum analysis, interviews, expert-validation sheets, response questionnaires, and a narrative-writing test, analyzed using Aiken's V validity index, inter-rater reliability, and percentage analysis. Results showed the product was highly valid, with Aiken's V of 1.00 for material, 0.95 for language, and 0.88 for graphic aspects. The practicality test indicated very high user acceptance, with a student response of 97.5% and a positive teacher response. Students' narrative-writing profile reached an average of 89% with 100% classical mastery, confirming the product is valid, practical, and effective.